Dimensional effect of doped porous ge using SILVACO TCAD simulation for potential optoelectronics application / A.F. Abd Rahim …[et al.] - Abd Rahim, A.F.; Mohamad Shuhaimi, N. S. I.; Mohd Razal, N. S.; Radzali, R.; Mahmood, A.; Hamzah, I.H.; Packeer Mohamed, M F (Universiti Teknologi MARA Cawangan Pulau Pinang, 2021)
Ge is considered to have several advantages over Si due to its high mobility and direct band gap, which makes it ideal for optoelectronic applications. The manipulation of bulk Ge into small structures has drawn a lot of interest due to the numerous distinctive properties caused by the impact of size quantization. Porous materials are ideally suited for sensing application due to their large effective surface area beside the fabrication of porous is simple. In this work, porous Ge is investigated for potential visible to near-infrared metal semiconductor metal (MSM) photo detector. The study investigated the performance and characterization of porous Ge (P-Ge) on Si substrate at different depths of porous (1 μm, 0.25 μm and 0.01 μm) by using SILVACO Athena and Atlas device simulator. Athena process simulator was used to construct the device structure while ATLAS device simulator was used to characterize the electrical and optical characteristics’ effect on the different sizes of the P-Ge fabricated on the Si substrate. The comparison of the porous devices were then made with bulk Ge devices (bulk Ge-on-Si, bulk Ge-on-Ge) to identify the exploitation of porosity resulted in a significant performance of current gains, spectral response, Schottky barrier height, and also photo and dark current. It was found that the P-Ge at 0.01 μm depth showed an improved current gain compared to other porous structures while bulk Ge-on-Si obtain greater current gain than bulk Ge-on-Ge. This evidence indicates that P-Ge produces a better performance of MSM photodetector than the bulk device. The spectral response of P-Ge shows a peak response at 800 nm, which is the near-infrared (IR) region supporting the feasibility of the P-Ge to be utilized for visible to near IR photo detection.